MANAJEMEN RISIKO KEUANGAN - Takdirmin; Sitti Zahra Amalia Faisal; Sitti Fatimah Rosalia Faisal; Andi Rizki Dani; Khaerunnisak Tahir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the dynamic era of globalization, financial risk management is a crucial aspect for companies to maintain stability and growth. This study aims to identify and analyze the challenges and opportunities in financial risk management, especially related to technological developments such as blockchain. The methodology used is a literature review, which includes an analysis of the latest literature on financial risk, mitigation strategies, and the application of technology in risk management. The results of the study indicate that financial risk management not only serves to protect company assets from loss, but also as a driver of innovation and efficiency. In addition, the adoption of technologies such as blockchain can increase transparency and security in risk management, although there are challenges in system integration and the need for digital literacy. This study concludes that a comprehensive and adaptive approach is needed to deal with uncertainty in today's business environment, and offers recommendations for more effective risk management implementation.